(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article investigates the linguocultural significance of dialectal vocabulary in English-speaking countries, focusing on how regionally marked lexical items encode cultural values, social identity, and historical experience. Dialectal words are examined not merely as linguistic deviations from the standard language but as culturally embedded units that reflect collective memory, local worldviews, and sociocultural norms. The study adopts a linguocultural approach combining semantic analysis, sociolinguistic interpretation, and contextual examination of dialectal usage in British, American, and Australian English. Particular attention is paid to the relationship between dialectal lexis and cultural identity, pragmatic meaning, and communicative function. The findings demonstrate that dialectal vocabulary functions as a linguocultural marker that mediates between language and culture, preserving regional traditions while shaping interpersonal communication. The research contributes to linguocultural studies by systematizing dialectal vocabulary as a meaningful cultural resource and highlighting its relevance for intercultural communication, language teaching, and cultural interpretation in English-speaking contexts.